The learning module for Muslim converts in Singapore : the roles of Darul Arqam - Nur Farhana binte Abdul Latiff (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
One of the most significant challenges new converts face is concerning seeking knowledge, especially nowadays when there is so much information available and so many contradictory views. It is difficult to know where to start, where to look and who to turn to. Thus, proper guidance and assistance needed for new converts to lead an appropriate way as Muslims. In Singapore, Darul Arqam plays a role of an organisation that provides courses and essential knowledge about Islam. This study focuses on examining the learning modules used by Darul Arqam before converts embracing Islam. It focuses on the three learning modules that adopted in propagating Islam to the participants. Each of these modules selected is considered necessary for the learning of Islam for the converts to be. In the study, the researcher interviewed two teachers and gave a questionnaire to participants of the learning modules to measure its effectiveness and relevancy of the modules to the new converts. The study also, found that the three learning modules used by Darul Arqam have benefited the participants in providing the knowledge and guidance of Islam. However, several problems have been identified regarding the three learning modules, namely Knowing Islam Session, Beginners' Course on Islam and Lets' Pray 1. This study will recommend some revisions, having a proper textbook, longer interacting duration, some courses to help build a relationship with converts. Hopefully, it can serve as preceding reviews of the modules.